HUBUNGAN RIWAYAT BBLR DENGAN STUNTING PADA ANAK BALITA DI KELURAHAN BORIBELLAYA KECAMATAN TURIKALE - Lydia Fanny; Sukmawati Sukmawti; Hikmawati Mas’ud; Sirajuddin (Media Gizi Pangan, 2023)
Toddler stunting is grouped as chronic nutritional problem which impact of many factors.The factor of children it self which can cause of stunting are low birth weight ( BBLR), the absence of breast feeding early, not exclusive of having breast milk, less quality and quantity of food companion to breast milk as well as infection disease. Based on health basic data research of the Minister of Health in 2010, 2013, and 2018 noted that national stunting cases were in a row at 35.6%, 37.2%, and 30.8%. In South Sulawesi found the cases were in a row 36.8%, 40.9%, and 35.6% While in Maros Regency stunting has prevalence rate at 34.87% in a short and shortest cases. Boribellaya area has the highest stunting prevalence in Turikale District is 13.8%. The purpose of this research was to know the relationships between Low Birth Weight and Stunting Cases in Boribellaya village. The techniques of research were observation and design cross sectional study. The research was conducted in June, 2021 at Boribelaya Village. The variables of the research were Low Birth Weight as independent variable and Stunting cases was dependent variable. Technique of data collection was interview of their identity and toddlers’ age. The stunting data collection was taken through secondary data from EPPGM 2021 by 52 children while for their birth weight was gotten from Book of Helth mother and child. The bias of this research found that not all or 28.8% (15 children) has not their birth weight notes in the Book of Mother and child. The long/height of the toddler were measured by using ribbon meter and not length board and microtoice.The population of this research was allof 52 toddlers which have stunting cases. Technique of sampling applied total sampling, while data analysis applied Bivariat Exact Fisher Test. The research result showed that the population age rate in 3-5 year was 59.6%, the gender was dominated by males in 59.6%. The higher with Low Birth Weight and without Low Birth Weight was 96.2%, Stunting was 73%, the child with severe stunting 27%, Low Birth Weight with stunting was 3.8%, The child With Low Birth Weight and stunting was 96.2% with the rate score was p=0.47 (>0.05). Based on above finding, it can be concluded that there is no correlation between Low Birth Weight and Stunting Cases at Toddler in Boribellava Village, Turikale District, Maros regency.